Antecedents And Outcome Of Compliance With Competition Act 2010 Of Public Listed Companies In Malaysia - Sankaran, Sasikala (2021)
The Competition Act 2010 (CA 2010) was gazetted in June 2010 and enforced in January 2012. The Malaysian Competition Commission (MyCC) was given the mandate to enforce the provisions of CA 2010 among the industry players at the market place. Although MyCC continuously conducts advocacy programmes to educate the public on CA 2010, and the level of promotion of competition in the marketplace increases, the number of complaints of anti-competitive conducts also increases over the years. Therefore, the purpose of this study is to ascertain the level of compliance with CA 2010 among the public listed companies (PLCs) of the Main Board of Bursa Malaysia and to examine the relationship between antecedents (1) the Board of Directors (BOD) Awareness and Knowledge, (2) Perception of Sanctions (Perceived Cost of Sanctions, Perceived Likelihood of Being Caught, Perceived Severity of MyCC’s enforcement, Perceived Risk), (3) Presence of Ethical Culture, and (4) the BOD Quality (Training) with Compliance to CA 2010 and the outcome on the Financial Performance of PLCs. This study also intends to examine the moderator interaction, Industry Type between the antecedents and dependent variable. The response rate of this study is 13% of which a total of 103 from the population of 780 completed and usable mailed survey questionnaires were returned by BODs or representatives of PLCs. The data were processed using SPSS for descriptive analysis and WarpPLS for measurement and structural models analysis.